ISLAMIZATION OF JAVANESE RITUAL: RUWAT SANTRI AS A REFLECTION OF INTERFAITH AND CULTURAL HARMONY IN INDONESIA - Anam, Saichul; Yusuf, Yusuf; Karim, Abdul (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
This study investigates the transformation of the Javanese ruwat ritual into ruwat santri, a symbolic Islamization that integrates Qur'anic recitation, while preserving local cultural traditions. It explores the social, spiritual and affective dimensions of the ritual using Weber’s social action theory and its implications for interfaith harmony and local religious practice The research adopts a qualitative-descriptive fieldwork design, including participant observation, in-depth interviews with religious leaders and ritual practitioners and ritual text documentation. The data analysis combines the Living Qur’an approach to understand the embodiment and meaning of Qur’anic recitation within this ritual context. Findings indicate that the transformation of Ruwat Jawa into Ruwat Santri constitutes a symbolic Islamization that preserves local cultural roots while embedding Quranic values into the ritual. Viewed through Weber’s framework, this practice integrates inherited tradition, emotional-spiritual experience, religious value commitment, and strategic adaptation to socio-economic realities. Community reception of the Quran in this context is performative and existential, treating it not merely as a sacred text but as a spiritual agent of blessing, protection and healing. The novelty of this study lies in highlighting the Quran as the primary actor in ritual transformation, surpassing previous studies that mainly focused on cultural acculturation. Practically, these findings have implications for cultural da‘wah strategies, tradition preservation aligned with Islamic law and the promotion of interfaith harmony. This research affirms that integrating Qur’anic values into local traditions fosters a contextual religiosity, enriching the discourse on the Living Qur’an in Indonesia. Abstrak Penelitian ini mengkaji transformasi ritual ruwat dalam tradisi Jawa menjadi ruwat santri, sebuah bentuk Islamisasi simbolik yang mengintegrasikan pembacaan Al-Qur’an sambil tetap melestarikan tradisi budaya lokal. Studi ini mengeksplorasi dimensi sosial, spiritual, dan afektif dari ritual tersebut dengan menggunakan teori tindakan sosial Max Weber, serta implikasinya bagi kerukunan antaragama (interfaith harmony) dan praktik keagamaan lokal. Penelitian ini menggunakan desain kerja lapangan kualitatif-deskriptif, meliputi observasi partisipatif, wawancara mendalam dengan tokoh agama dan pelaku ritual, serta dokumentasi teks ritual. Analisis memadukan pendekatan Living Qur’an untuk memahami perwujudan dan makna pembacaan Al-Qur’an dalam konteks ritual ini. Temuan penelitian menunjukkan bahwa transformasi ruwat Jawa menjadi ruwat santri merupakan Islamisasi simbolik yang mempertahankan akar budaya lokal sekaligus menyematkan nilai-nilai Qur’ani ke dalam ritual. Dalam kerangka teori Weber, praktik ini mengintegrasikan tradisi warisan, pengalaman emosional-spiritual, komitmen terhadap nilai-nilai agama, dan adaptasi strategis terhadap realitas sosial-ekonomi. Penerimaan masyarakat terhadap Al-Qur’an dalam konteks ini bersifat performatif dan eksistensial, menempatkannya bukan hanya sebagai teks suci, tetapi juga sebagai agen spiritual pembawa berkah, perlindungan, dan penyembuhan. Kebaruan penelitian ini terletak pada penekanan Al-Qur’an sebagai aktor utama dalam transformasi ritual, melampaui kajian-kajian sebelumnya yang umumnya berfokus pada akulturasi budaya. Secara praktis, temuan ini memiliki implikasi bagi strategi dakwah berbasis budaya, pelestarian tradisi yang selaras dengan syariat Islam, serta penguatan kerukunan antaragama. Penelitian ini menegaskan bahwa integrasi nilai-nilai Qur’ani ke dalam tradisi lokal membentuk religiositas kontekstual, sekaligus memperkaya wacana Living Qur’an di Indonesia..